Channel Choice in Live Streaming Commerce - Li, Yina; Ning, Yu; Fan, Weiguo; Kumar, Ajay; Ye, Fei (Production and Operations Management, 2024)
Live streaming has significantly transformed the landscape of both offline and online retail operations. This article explores the optimal timing and circumstances under which a firm with a specific product should launch a live streaming channel, and if so, whether it should use third-party streaming, self-run streaming, or a combination of both. We demonstrate that no single channel structure is universally superior to the others: the firm's optimal channel strategy depends on the third-party streamer's popularity and bargaining power, the investment and broadcasting effort cost for the live streaming channel, consumer's channel preference and extra cost for watching live streaming, cross-channel spillover, as well as the price sensitivity of a product. In general, live streaming is most beneficial for firms selling products that aren't highly price sensitive, where traditional pricing tool is less important for attracting consumers. Start-ups should collaborate with either highly popular streamers or those with a small but dedicated following, avoiding those with intermediate popularity. In contrast, established firms should partner with streamers who have a moderate level of popularity. An established firm considering leveraging two or more channels concurrently should additionally take into consideration the cross-channel spillover, channel encroachment cost, and channel competition. Our research reveals that, contrary to expectation, price in live streaming channels may not always be lower than those in traditional channels. Furthermore, highly popular streamers do not always demand higher revenue-sharing ratios and slotting fees. This research sheds light on the key decisions for firms considering live streaming commerce: whether to adopt it, when to integrate it into their strategy, and how to effectively implement it.